Analisis penerapan Good Governance terhadap pelayanan publik di Kantor Kecamatan Baturaja Barat - Oktavia, Anisa; Trisninawati, Trisninawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Good governance is a definition that summarizes the end of the New Order regime and was changed by reform acts; in this era, it is necessary to change the power system that challenges the clean and democratic process. This study aims to determine the implementation of the importance of good governance, public services, and the effect of good governance implementation on public services at the West Baturaja District Office. This research uses a quantitative methodology that uses incidental sampling techniques. Data collection was done through questionnaires, observation, and documentation. The methodology used is descriptive statistical analysis and inferential statistics (product moment correlation test) using the SPSS 25 software application. The results of the descriptive analysis show that the application of good governance and the quality of public services at the West Baturaja District Office are in the good category in terms of indicators. The results of the correlation analysis between the importance of public service moments and the effect of good governance on it is 0.888% which is positive, this shows that the effect is very strong.